Reformasi Birokrasi dalam Peningkatan Kualitas Pelayanan Publik pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPM-PTSP) Kabupaten Karo - Herda Sri Rahayu Sebayang; Marlon Sihombing; Warjio Warjio (Universitas Medan Area, 2022)
Bureaucratic Reform in public services aims to improve the quality of public services in accordance with the needs and expectations of the community. The purpose of this study is to analyze how the process of implementing bureaucratic reform in improving the quality of public services and how to achieve bureaucratic reform in improving the quality of public services at the Investment and One-Stop Integrated Service Service (DPM-PTSP) of Karo Regency. This research uses qualitative research methods with a descriptive approach, and primary data collection techniques (observations, interviews) and secondary data (documentation studies). Based on the results of the study, it can be concluded, after the bureaucratic reforms were implemented, the aspects that support public services at DPM-PTSP experienced changes and improvements in both organizational structure, human resources, simplification of deregulation, the use of technology that makes it easier to issue permits, and even business actors have been able to issue permits independently without face-to-face with DPM-PTSP officers. The implementation of bureaucratic reforms has increased the quality of public services and supports the acceleration of business in Karo Regency.